Diamond anvils with a round table designed for high pressure experiments in DAC. Issue 4 (2nd October 2017) - Dubrovinsky, Leonid; Koemets, Egor; Bykov, Maxim; Bykova, Elena; Aprilis, Georgios; Pakhomova, Anna; Glazyrin, Konstantin; Laskin, Alexander; Prakapenka, Vitali B.; Greenberg, Eran; Dubrovinskaia, Natalia
ABSTRACT: Here, we present new Diamond Anvils with a Round Table (DART-anvils) designed for applications in the diamond anvil cell (DAC) technique. The main features of the new DART-anvil design are a spherical shape of both the crown and the table of a diamond and the position of the centre of the culet exactly in the centre of the sphere. The performance of DART-anvils was tested in a number of high pressure high-temperature experiments at different synchrotron beamlines. These experiments demonstrated a number of advantages, which are unavailable with any of the hitherto known anvil designs. Use of DART-anvils enables to realise in situ single-crystal X-ray diffraction experiments with laser heating using stationary laser-heating setups; eliminating flat-plate design of conventional anvils, DART-anvils make the cell alignment easier; working as solid immersion lenses, they provide additional magnification of the sample in a DAC and improve the image resolution.